2013
DOI: 10.1093/treephys/tpt103
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting water strategies of two Mediterranean shrubs of limited distribution: uncertain future under a drier climate

Abstract: Plants have evolved different strategies to cope with drought, involving alternative ecophysiologies and different levels of plasticity. These strategies are critical for species of limited distribution, which are especially vulnerable to the current rates of rapid environmental change. The aim of this study was to assess the water strategy of two species with limited distribution, Cneorum tricoccon L. and Rhamnus ludovici-salvatoris Chodat., and evaluate their interpopulation variability along an aridity grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 73 publications
2
17
0
Order By: Relevance
“…forest disturbance and forest management, mortality and succession of vegetation, which are considered as a key challenge for ecohydrology and forest science disciplines (Newman et al, 2006). Finally, a finer scale of analysis and modeling would have allowed to distinguish water strategies under water stress between species (Lázaro-Nogal et al, 2013). Nevertheless, our findings are valuable for gaining understanding on the nexus between water planning and land management in the UTB and by enlargement for the Júcar river basin.…”
Section: Discussionmentioning
confidence: 90%
“…forest disturbance and forest management, mortality and succession of vegetation, which are considered as a key challenge for ecohydrology and forest science disciplines (Newman et al, 2006). Finally, a finer scale of analysis and modeling would have allowed to distinguish water strategies under water stress between species (Lázaro-Nogal et al, 2013). Nevertheless, our findings are valuable for gaining understanding on the nexus between water planning and land management in the UTB and by enlargement for the Júcar river basin.…”
Section: Discussionmentioning
confidence: 90%
“…In fact, it can be hypothesized that apparent differences in water-use strategies could explain the differences in the ecological niches they occupy. Contrasting water-use strategies have been already reported both among co-occurring species, including Mediterranean shrubs, from diverse taxonomic groups (Hernandez et al 2010, Quero et al 2011, MorenoGutierrez et al 2012, Lázaro-Nogal et al 2013 as well as within a single genus (David et al 2007, Tognetti et al 2007. The coexistence of different strategies within a certain area or ecosystem has been typically related to differences in plant functional traits (Filella and Peñuelas 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown species‐specific variations in plant δ 13 C associated with spatial and temporal (or seasonal) precipitation changes in drylands (Golluscio & Oesterheld ; Lázaro‐Nogal et al . ). These species‐specific responses are related to inter‐specific differences in water use strategies (Golluscio & Oesterheld ; Moreno‐Gutiérrez et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, the importance of C and N isotope variations in the same plant species growing along rainfall gradients has been neglected (but see Lázaro‐Nogal et al . ), and studies of this variation could enhance our understanding of species‐specific plant responses to precipitation changes in water‐limited ecosystems.…”
Section: Introductionmentioning
confidence: 99%